Improving outcomes of hematopoietic stem cell transplant for leukemia in children and young adults in resource-limited setting - Garima Nirmal; Subhashish Paul; Vaibhav Chadha; Shreyasi Das; Mohit Chaudhary; Manju Joseph; Bharti Sharma; Himshikha Yadav; K.K. Swathymon; Iskandarov Kamol; Gaurav Kharya (Elsevier, 2024)
Introduction: Allogeneic hematopoietic stem cell transplantation (HSCT) is a curative approach in patients with relapsed and high-risk leukemia. This retrospective analysis aimed to investigate outcomes and risk factors associated with HSCT in children and young adults with hematological malignancies in a resource-limited setting. Methods: We retrospectively evaluated 48 pediatric and young adult patients diagnosed with hematological malignancies who underwent HSCT at our institution between April 2017 and Jan 2023. Result: The median age of the cohort was 10 years (6 months - 21 years), and the majority of patients underwent transplants for acute lymphoblastic leukemia (ALL) (n = 24; 50 %) and acute myeloid leukemia (n = 18; 37.5%). Median time to neutrophil and platelet engraftment were 15 days (range 9-28) and 18 days (range 9-40), respectively. One patient had primary graft failure. Cytomegalovirus reactivation occurred in 21 patients (43.8%). Seventeen patients received escalated donor lymphocyte infusion (DLI). With a median follow-up of 902 days (52-2490), the probability of event free survival and overall survival (OS) was 65.9% and 69.4%. OS for lymphoid and myeloid malignancies were 64.7% and 75.2%, respectively. Kaplan-Meier probabilities of OS for patients in first complete remission (CR), CR2, CR3, or with refractory disease were 80%, 76.2%, 0%, and 40%, respectively (p = 0.02). OS of the patients undergoing matched sibling donor (n = 17) or haploidentical HSCT (n = 31) was 70.6% and 69%, respectively (p = 0.989). Conclusions: Our study demonstrates excellent outcomes of patients with hematological malignancies undergoing allogeneic HSCT with similar outcomes in HLA-identical sibling donors and haploidentical first-degree family donors. Prophylactic DLI might be considered in patients with high-risk leukemia to prevent relapse, including ALL.